Pharmacognostic and Phytochemical Features of Cleome gynandra Whole Plant and its Powder: Life Sciences-Microbiology - K, Chitra Devi; G, Subhashini; S. K., Sundar; S, Rajan (International Journal of Life Science and Pharma Research, 2022)
Cleome gynandra is one among the plants used as a remedy for various human and animal diseases. It is commonly called nalvelai in Tamil and belongs to the family cleomaceae. Aim of the present study is used to assess quality of the powdered plant materials. The prime objective of this study is to assess characteristic features of powder preparation, pharmacognostic value like ash value, extractive value, chromophore by fluorescent assay and also to study phytochemical markers. Powder microscopy, organoleptic character assessment, physiochemical, fluorescent features, microbial load and preliminary phytochemical features like pharmacognosy of this plant were studied by making use of standard textual procedures. Plant powder is yellowish green in colour with a bitter taste. Plant powder showed 0% foreign matter, 4.9%w/w total ash with higher water extractive (23.7%w/w). Variable chromophores were detected with different acid and alkali treatment. Treatment of nitric acid showed violet brown coloration under long UV radiation. Microbial load was within the limits of pharmacopeial standards of raw drugs and no pathogenic organisms were detected. All the pharmacognostic results were within the limits of ayurvedic pharmacopeia of India. Whole plant powder showed the presence of terpenoids, flavonoids, polyphenols and saponins, which could be a phytochemical marker. GC-MS report revealed the presence of 20 Compounds in crude powder preparation. Histochemical study also confirmed the presence of tannin, saponin, flavonoids, steroids, Terpenoids and polyphenols, which could also confirm the water-soluble compounds in the C. gynandra whole plant powder. These observations would be of immense value in the botanical identification and standardization of drugs in a crude form.